DAMPAK PEMBAKARAN BATUBARA INDONESIA TERKAIT KANDUNGAN PRODUK GAS BUANG - Nur Aryanto Aryono (Badan Pengkajian dan Penerapan Teknologi, 2006)
The output of electricity for power plants and output of steam for industrialfurnaces related with flue gas concentration, such as fly ash (dust), CO, CO2NOx, and SO2. The condition of flue gas product is very important for estimatedthe actual level of emissions, because it product depends on type of plant,operating conditions, maintenance, and on fuel properties. The consequence ofcoal combustion, a considerable increase in emissions of dust, hydrocarbon,NOx and SO2 is to be expected. Therefore, to use the abatement technology,such as filters, desulphurization plants, de-nitrification unit, fluidized bedcombustion, and integrated gas combined cycle power plants for reducing theconcentrations of flue gas is an appropriate choice.Kata kunci: coal combustion, flue gas, emission